LINGUISTIC STUDY OF INTRALINGUAL LACUNAES OF THE UZBEK LANGUAGE (World Bulletin of Social Sciences, 2024)
The notion of lacuna, its classification and cases of delineation in the process of intercultural communication are considered in this article. Also a special attention is paid to adequacy in translation by the example of comparing the English, Russian and Uzbek languages